Dynamic Interplay of Pharmacy Learners During a Solid Organ Transplantation Learning Experience. (June 2018) - Sin, Jonathan H.; Li, Hanlin; Jandovitz, Nicholas; King, Madeline; Tsapepas, Demetra S.
Institutions with established clinical pharmacy services have the ability to offer focused patient care learning experiences, often led by a clinical specialist, for pharmacy residents and pharmacy students. Since all parties are continually involved in professional development and lifelong learning, the aforementioned groups can all be considered "pharmacy learners." By utilizing the dynamic interplay and collaboration between pharmacy learners through direct and nondirect patient care activities, experiential and educational opportunities may be improved and enhanced for each learner. A tiered learning approach engages individuals in areas such as direct patient care, patient education, presentations, research projects, career development, and the feedback process. We describe our experience during a solid organ transplantation learning experience using a layered learning practice model that included a clinical pharmacy specialist, a postgraduate year 2 specialty pharmacy resident, a postgraduate year 1 pharmacy resident, and a pharmacy student.